A propósito del sentido de lo humano en la empresa: ¿utopía o realidad?, la disonancia entre la retórica del discurso administrativo y las prácticas de gestión humana (2019)
The article seeks to approach the construction of a theoreticaldiscourse that is evident in companies about human talentmanagement. For this, the author takes into consideration ashis main base conceptual referents of the New ThoughtAdministrative school derived from "Life Sciences andManagement", and tries to leave open the discourse andreflection on the dissonance between what we think,pronounce and write by the management and its executivesand the real action derived from their practices, which seem tobe, it is necessary to begin training for management to ensure areal change in this matter.The phenomenon allows uncovering the absence of aconsistent and integral humanism in an artificial socialorganization, which generates openness and the possibility tochallenge human management practices yet to find an appliedconnotation that is expected not to pass only by innovation andingenuity.Therefore, rather than a problem of "process and rhetoric inthe speech" radical humanism in administration finds now aproblem of meaning and hierarchy of its imperatives, where itseems to be carried by significant advantage of individualismand financial performance